Use of the Bezier Curves for a Vehicles Driving Cycles’ Modeling - Valerii Dembitskyi (Communications - Scientific letters of the University of Zilina, 2021)
While performing the research of the vehicles operating characteristics in real operating conditions, a question of creation or correction of a movement driving cycle always appears. An absence of a mathematical model rather complicates the research process and makes a quick correction of movement conditions impossible. To solve the given problem, it was proposed to model a driving cycle using the Bezier curves. As a result of this research, it is stated that the most advantageous is to use the Bezier curves of the second and third degrees. During the analysis of results of driving cycles modeling and their comparison to the standardized and real movement cycles, a satisfactory coincidence of results was obtained. The conducted thematic research confirms the previous results, directed to creation of a universal dynamic model of a vehicle’s driving cycle.